Effect of Addition Extract Fermented Catfish Waste Microcapsules in Feed Ration on Red Blood Profile Broiler Chickens - Dani, Muhamad Ikram; Abun; Adriani, Lovita (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aimed to analyze the effect and impact of addition fermented catfish waste extract microcapsules in feed ration on the red blood profile of broiler chickens. This research was conducted at the Ciparanje Experimental Facility, Faculty of Animal Husbandry, Padjadjaran University from September-November 2024. This research used a Completely Randomized Design (CRD) with 5 treatments and 4 replications. Each replication consisting of 4 chickens with a total of 80 broiler chickens in this study. The research treatments were P0: ration without the addition of catfish waste extract microcapsules (basal ration), P1: 99.5% basal ration + 0.5% catfish waste extract microcapsules, P2: 99% basal ration + 1% fermented catfish waste extract microcapsules, P3: 98.5% + 1.5% fermented catfish waste extract microcapsules, and P4: 98% fermented catfish waste extract microcapsules. basal + 2% microcapsules of fermented catfish waste extract. The parameters measured are the red blood profile including the number of erythrocytes, hemoglobin levels, hematocrit values, and mean corpuscular volume (MCV). The results of statistical analysis showed that effect were significant (P<0.05) increase on the number of erythrocytes, hemoglobin levels, and hematocrit values, but not significantly different (P>0.05) on the MCV. The research conclusion was that the addition of fermented catfish waste extract microcapsules in the ration had an effect on the number of erythrocytes, hemoglobin levels, and hematocrit values, but does not have a significant effect on the MCV of broiler chickens. MELIPF can be added at a usage rate of 0.5-2% in the ration.